The Effectiveness of AKD as Internal Sizing and Surface Sizing on Improving Barrier Properties of Medium Paper - Mochammad Iqbal Fardiansyah; Nurul Ajeng Susilo; Edwin K. Sijabat; Erwin Erwin; Gilang Garnadi Suryadi (Department of Chemical Engineering, Politeknik Negeri Bandung, 2025)
Recycled fiber is an alternative raw material that can be produced into new paper called medium paper. Medium paper has important parameters that need to be considered when making process, one of which is cobb size. Based on data processed at the factory, cobb size instability occurs and tends to increase beyond the standards set by the factory. An increase in the cobb size parameter occurs due to a lack of optimal sizing, causing a decrease in the paper's ability to hold air and can reduce the dimensional stability and surface quality of the paper. Improving the quality of the paper produced is necessary. In this research, chemical sizing agents were added such as AKD (Alkyl Ketene Dimer) which aims to determine the effect of adding AKD to recycled raw materials with variations in the right dose when injected as internal sizing and surface sizing to reduce cobb size value. By using a dose of Alkyl Ketene Dimer (0 kg/ton, 0.5 kg/ton, 1 kg/ton) as internal sizing and surface sizing and the effect of AKD curing time-2 days. At the best dose, the cobb size value was obtained, namely 62 gr/m² and there was an increase in the quality of Cobb size paper compared to existing by 30%. This shows that longer curing time results in a more hydrophobic surface and lower water absorption, indicating an improvement in the paper water resistance.